2013
DOI: 10.3844/ajisp.2013.120.129
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Gc-Macrophage Activating Factor in Human Neurons; Implications for Treatment of Chronic Fatigue Syndrome

Abstract: Myalgic Encephalomyelitis/Chronic Fatigue Syndrome (ME/CFS) is a debilitating disease of multifactorial aetiology characterized by immune system dysfunction, widespread inflammation, multisystemic neuropathology and persistent pain. Given the central role of the immune system in the pathogenesis of the syndrome, we studied the effects of a potent modulator of the immune system in in vitro and in vivo models that could help clarifying its role and indications in ME/CFS treatment. To this end, we studied the eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 36 publications
0
0
0
Order By: Relevance
“…Different research teams have reported the anticancer activity of the macrophage-activating factor [10][11][12][13][14][15][16][17][18][19]. GcMAF was shown to have an ability to rectify neurodegenerative diseases including autism spectrum disorder [7,[20][21][22][23]. The conducted experiments demonstrate that the wide range of therapeutic properties of GcMAF is directly related to its impact on the macrophage [8,9,[24][25][26].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Different research teams have reported the anticancer activity of the macrophage-activating factor [10][11][12][13][14][15][16][17][18][19]. GcMAF was shown to have an ability to rectify neurodegenerative diseases including autism spectrum disorder [7,[20][21][22][23]. The conducted experiments demonstrate that the wide range of therapeutic properties of GcMAF is directly related to its impact on the macrophage [8,9,[24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…Those are examples of the so-called secondgeneration GcMAF, which actually is a mixture of enzyme-treated plasma proteins, and the so-called third-generation GcMAF, which is colostrum containing terminal, unbound GalNAc [26,[32][33][34]. In our early studies of GcMAF, we faced the complicacy of the procedure of isolating DBP from plasma and converting it to GcMAF [11,21,35,36]. In the present study, we elaborated the original method for both producing and converting GcMAF as well as analyzing its activation potency.…”
Section: Introductionmentioning
confidence: 99%